AB0683 Prevalence of the Metabolic Syndrome According to Various Definitions in Patients with Ankylosing Spondylitis. (10th June 2014) - Papagoras, C.; Markatseli, T.E.; Milionis, H.J.; Kaltsonoudis, E.; Voulgari, P.V.; Drosos, A.A.
Abstract : Background: There is evidence that inflammatory joint disease is associated with increased cardiovascular risk. Systemic inflammation and reduced physical activity may be involved through changes in insulin sensitivity and obesity, thus allowing for the emergence of the metabolic syndrome. Objectives: To study the prevalence and components of the metabolic syndrome in patients with ankylosing spondylitis (AS) in comparison with healthy controls. Methods: Non-diabetic patients with AS followed at a single center and age- and sex- matched healthy controls were included in the study. The metabolic syndrome was defined according to the National Cholesterol Education Program: Adult Treatment Panel III (NCEP:ATP III), the American Heart Association/National Heart, Lung and Blood Institute (AHA/NHLBI), the International Diabetes Federation (IDF) and the Joint Interim Statement (JIS) criteria 1 . Results: Seventy-six AS patients and 63 healthy controls were included. Patients were more often smokers (p<0.001) and had significantly lower HDL (p=0.002) and triglyceride levels (p=0.018) than controls. According to the NCEP:ATP III, AHA/NHLBI, IDF and the JIS criteria respectively, 9.2%, 13.2%, 22.4% and 23.7 of AS patients had the metabolic syndrome compared to 6.3%, 9.5%, 19% and 19% of healthy controls (p=NS between patients and controls for all metabolic syndrome definitions). Focusing on the individual metabolic syndrome criteria, no criterion was fulfilled significantly more often by AS patients compared to controls, although the "low HDL" criterion reached near-significance (p=0.083). Conclusions: The proportion of AS patients with the metabolic syndrome varies widely according to the definition used. However, the metabolic syndrome does not seem to be more prevalent in the AS patients compared to healthy controls despite having lower HDL cholesterol. References: Circulation. 2009;120:1640-5. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3141